Multilingual Philippine medical thesaurus on diseases - pathological conditions, signs and symptoms in Iluko - Simbulan, Mary Grace C. (School of Library and Information Studies, University of the Philippines Diliman, 2003)
The medical thesaurus plays a significant role in the field of medical informatics. The medical thesaurus provides terms or noun phrases understandable by both medical practitioners and clients. It assists the medical practitioners in understanding terms or concepts because of its scope notes. It provides a common language for the medical field making information processing efficient. While other countries are starting to incorporate information technology to better perform health information services, our country is yet to establish its own medical thesaurus. Language barrier is one of the reasons why a Philippine Multilingual Medical thesaurus has not yet been constructed. The study attempted to translate the class C23 - Diseases, Pathological Conditions, Signs and Symptoms of Medical Subject Headings (MESH 2003) into Iluko.